Evaluación del proceso de reincorporación a excombatientes mediante un sistema ganadero en Tibú, Colombia - Néstor Sánchez Botello; Gladys Montañez Acevedo (Mundo Fesc)
Social and armed conflicts in Colombia, El Salvador, and Nicaragua began in the 20th century primarily due to difficult access to land and the lack of political participation by new idealistic movements. After 52 years of conflict in Colombia, negotiations between the government and the armed group Revolutionary Armed Forces of Colombia, People's Army (FARC-EP) began. Thus, on September 26, 2016, the Peace Accords were signed, and collective productive projects for ex-combatants in various areas of the country were proposed as an alternative. In 2020, the idea of ​​evaluating the reincorporation process, along with the livestock project of a group of ex-combatants in the Caño Indio area of ​​the municipality of Tibú, was born. To this end, a purposive non-probability sampling was used, and 16 families with this status were selected. The research approach was mixed, using a survey-type questionnaire with 40 closed, multiple-choice, and opinion-based questions. Additionally, workshops and focus groups were held to advance the research and provide training. A SWOT matrix was designed using Participatory Action Research (PAR). The results showed that the ex-combatants, following the implementation of the livestock project, completed the path to reintegration into civilian life. 100% expressed their commitment to the Peace Accords and new alternatives for economic and social development. They also contributed to developing strategies to consolidate the community project.